2017
DOI: 10.1016/j.jvs.2016.12.142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of distal entry tears in acute type B aortic dissection after thoracic endovascular aortic repair

Abstract: This study demonstrated that TEVAR for ATBAD had low perioperative morbidity and mortality and satisfactory midterm outcome. Distal entry tears increase the occurrence of late aortic events and inhibit aortic remolding but do not have a significantly negative effect on late survival. Repairing all entry tears to restore single-lumen blood flow and enhance false lumen thrombosis might benefit selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…A class IIa recommendation for endovascular repair in uncomplicated TBAD to achieve false-lumen thrombosis has been issued (29); however, the nonnegligible risk of stroke and paraplegia (6) derived from early preemptive endovascular treatment calls for the development of selective imaging-based strategies. On the other hand, the false lumen is patent in 13%-60% of patients with TBAD after endovascular repair (6,20) and in 31%-77% of patients with TAAD after initial surgery (5,10,21,24), and remaining tears have been related to long-term AAEs (19)(20)(21). Several endovascular techniques for achieving thrombosis of the postsurgical false lumen through DT repair have been developed as an alternative to open surgery (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A class IIa recommendation for endovascular repair in uncomplicated TBAD to achieve false-lumen thrombosis has been issued (29); however, the nonnegligible risk of stroke and paraplegia (6) derived from early preemptive endovascular treatment calls for the development of selective imaging-based strategies. On the other hand, the false lumen is patent in 13%-60% of patients with TBAD after endovascular repair (6,20) and in 31%-77% of patients with TAAD after initial surgery (5,10,21,24), and remaining tears have been related to long-term AAEs (19)(20)(21). Several endovascular techniques for achieving thrombosis of the postsurgical false lumen through DT repair have been developed as an alternative to open surgery (30).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, data from in vitro studies suggest that the presence of a large DT with a small PT or without a PT also increases false-lumen pressure (16)(17)(18). Furthermore, the presence, location, and size of remaining tears have been related to postoperative distal aortic enlargement after treatment of the PT in TAAD and TBAD (19)(20)(21).…”
mentioning
confidence: 99%
“…14 Persistent distal filling of FL is a major cause of treatment failure and/or reintervention after stentgraft treatment of cTBAD, with 30-50% of delayed aortic reinterventions related to distal entry. 6,[21][22][23][24][25] The importance of DET at the level of the visceral aorta is well demonstrated both clinically and experimentally in animal experiments and computational models designed to predict FL thrombosis after TEVAR in TBAD. 14,18,21,[26][27][28][29][30][31][32][33][34][35] One systematic review examining eight studies of TEVAR in TBAD, with a total of 1249 patients and median follow-up of 27 months, noted that DET constituted the most common cause for reintervention (40.5% compared to 31.6% for proximal failures).…”
Section: Summary Of Critical Literature Analysismentioning
confidence: 99%
“…Another recent study evaluating the outcomes of TEVAR in aTBAD showed persistent FL filling through DET in 105 of 130 patients (81%), with the majority (63%) arising in the visceral aorta, and noting a higher rate of complete FL thrombosis in patients who did not have DET. 21 An experienced group recently reported on the use of fenestrated endovascular artic repair (FEVAR) in six patients with progressive FL aneurysm growth after initial treatment of acute TBAD (aTBAD), with virtually all representing failures due to persistent DET. 25 Certain types of type-II endoleak can play a major role in FL expansion after endovascular treatment of aortic dissections.…”
Section: Summary Of Critical Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation